Driving economic resilience: assessing cash waqf’s influence on micro-business sustainability in Malaysia / Soliha Sanusi ... [et al.] - Sanusi, Soliha; Mohd Shafiai, Muhammad Hakimi; Muhammed, Aliyu Dahiru; Mohamad Dalian, Nur Izzaty; Ghazali, Aziatul Waznah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
As the government of Malaysia continues to focus on the welfare of the Bottom 40 (B40) per cent of the population, sometimes referred to as the B40 community, there has been a discernible reduction in the country’s poverty level. Hence, waqf is an endeavour to enhance society as it has improved socioeconomic conditions since the time of the Prophet Muhammad (PBUH). Nevertheless, entrepreneurs have received little attention due to waqf constraints, which hold that the waqf fund cannot be reduced from its initial worth. Therefore, this study aimed to explore the impact of the cash waqf program, which Waqaf An-Nur Corporation Berhad administers, has had on the micro businesses that have received funding in Johor, the southern part of Malaysia. A qualitative method was employed, and several interview sessions were held with four (4) respondents. According to the findings, the entrepreneurs agreed that the programs that Waqaf An-Nur Corporation Berhad provided had benefited them in various ways, including enhancing their marketing strategies and increasing their capital, number of customers, and sales. This study can contribute to the existing literature on the waqf sector, particularly cash waqf, and invite other institutions to participate in a waqf project aiding businesses through the Islamic social finance sector. Future research shall explore the success of cash waqf in other domains, such as the health and education sectors, and the application of technology, such as digital platforms and blockchain, in waqf institutions.